E Evaluasi Program Sekolah Perempuan untuk Perdamaian The Asian Muslim Action Network (AMAN) Indonesia di Jakarta - Siti Hanifah (Jurnal Evaluasi Pendidikan, 2020)
This study is an evaluative program with reference to the Logical Framework Analysis evaluation model with a focus on the situation, input, output, outcome and impact. The research was conducted in 2016 at Pondok Bambu Jakarta Timur. The subjects in the study includes participants of Women School for Peace the families, facilitators, and stakeholders both from government and community leaders to see the change of situation, individual transformation of participants, relational, structural and cultural element in the community. Data collected through observation, deep interviews, and documentation analysis. Data analysis technique used the descriptive data analysis to interpret the data from every aspect that was evaluated, then compared with predefined criteria. The results of evaluation show that there were situation had changed from disharmony community where previously they don`t care each other to community who aware with their social problems. The social cohesion among community members and the recognition of women leadership are the main indicators of the achievement. While the input aspect that includes participants, facilitators and modules, how they support the processes of learning. The program output shows significant change on participants individual transformation that reveal their capacity as new female leader as well as the peace agent. The outcome aspect shows that the relational transformation occurred between the participants and the spouse, the family and the surrounding community that indicated by having better communication. The impact of the program as measured by structural and cultural transformation reveals that the program contributes to the emerging peace-building policies and cultures. The Women's School for Peace program has demonstrated a comprehensive effort in the conflict transformation. Keywords: Women School for Peace, Logical Framework Analysis program evaluation model, conflict transformation.